Body-conformation traits and their association with milk yield in Bos indicus dairy cattle - Dominguez-Castaño, Pablo; Vasconcelos-Silva, J Augusto II (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: The search for productive and efficient animals in dairy cattle leads to selecting cows by milk yield and morphological traits, such as body-conformation and udder traits suitable to maintain production and permanence in the herd. Body conformation traits have been targeted in dairy cattle breeding because they are associated with lifetime production and, consequently, influence both the welfare and profitability of dairy cattle, by affecting health and leading to the premature culling of cows. Objective: This review aims to explore the genetic importance of linear conformation traits related to “frame”, “foot and leg” and “mammary system”, explaining their relationship with milk production, with a particular focus on Zebu breeds. Conclusion: Heritability estimates for body conformation traits related to the mammary system and structure, as well as for milk production, indicate that changes can be achieved through selection. Some body conformation traits were found to be correlated with milk yield, which suggests that selection to increase milk yield should be approached with caution as it may, in the long term, lead to undesirable changes in conformation traits of the body dimension and mammary system.